Gelatin Nanoparticles for Complexation and Enhanced Cellular Delivery of mRNA - Lea Andrée; Rik Oude Egberink; Josephine Dodemont; Negar Hassani Besheli; Fang Yang; Roland Brock; Sander C. G. Leeuwenburgh (Nanomaterials, 2022)
Messenger RNA (mRNA) is increasingly gaining interest as a modality in vaccination and protein replacement therapy. In regenerative medicine, the mRNA-mediated expression of growth factors has shown promising results. In contrast to protein delivery, successful mRNA delivery requires a vector to induce cellular uptake and subsequent endosomal escape to reach its end destination, the ribosome. Current non-viral vectors such as lipid- or polymer-based nanoparticles have been successfully used to express mRNA-encoded proteins. However, to advance the use of mRNA in regenerative medicine, it is required to assess the compatibility of mRNA with biomaterials that are typically applied in this field. Herein, we investigated the complexation, cellular uptake and maintenance of the integrity of mRNA complexed with gelatin nanoparticles (GNPs). To this end, GNPs with positive, neutral or negative surface charge were synthesized to assess their ability to bind and transport mRNA into cells. Positively charged GNPs exhibited the highest binding affinity and transported substantial amounts of mRNA into pre-osteoblastic cells, as assessed by confocal microscopy using fluorescently labeled mRNA. Furthermore, the GNP-bound mRNA remained stable. However, no expression of mRNA-encoded protein was detected, which is likely related to insufficient endosomal escape and/or mRNA release from the GNPs. Our results indicate that gelatin-based nanomaterials interact with mRNA in a charge-dependent manner and also mediate cellular uptake. These results create the basis for the incorporation of further functionality to yield endosomal release.